Harm reduction self-efficacy and motivations for contactless supply access among a sample of syringe services program participants - Rachel A. Hoopsick; Benjamin M. Campbell; R. Andrew Yockey (Harm Reduction Journal)
Abstract Background Contactless harm reduction supply methods (e.g., vending machines, mail order, mobile delivery) have become prevalent in the United States. However, this approach has faced some criticisms, including the notion that, unlike staffed syringe services programs, contactless methods do not provide face-to-face support, education, or referrals to treatment, potentially limiting their overall impact. Methods We collected self-reported data from a sample of people who inject drugs who accessed a syringe services program (N = 50), including their demographics, harm reduction self-efficacy (i.e., confidence to employ specific health-preserving coping skills in high-risk drug using situations), and motivations for contactless harm reduction supply access via vending machine. We explored differences in the participants' demographics and harm reduction self-efficacy by usual method of harm reduction supply access (in-person vs. vending machine). Results Participants accessed the harm reduction supply vending machine primarily out of convenience (66%) and limited syringe services program hours (56%). Fear of being seen by someone they knew (28%), law enforcement (34%), and social services (22%) were also motivators. Overall, harm reduction self-efficacy was highest for safer injection practices but lowest for reducing drug use. We did not find any significant differences in participants’ demographics or harm reduction self-efficacy by access method. Conclusions People who access harm reduction supplies in person and through contactless methods may not meaningfully differ in terms of their demographics and harm reduction self-efficacy, and contactless harm reduction supply methods are more convenient than in-person services. Findings support continued reductions to barriers of harm reduction services.